Europium activating β-type sialon phosphor, and light-emitting device
By adding yttrium, titanium, gadolinium, or alkaline earth metals to europium-activated β-sialon phosphors within specified ranges, crystal defects are minimized, enhancing internal quantum efficiency and luminous efficiency.
Patent Information
- Application Number
- JP2024177855
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-09-10
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-09-06
AI Technical Summary
Existing europium-activated β-sialon phosphors suffer from reduced internal quantum efficiency due to crystal defects, which affect their luminous efficiency.
Incorporating predetermined amounts of yttrium, titanium, gadolinium, or alkaline earth metals such as magnesium and strontium into the europium-activated β-sialon phosphor composition, within specific content ranges, to fill vacancies and reduce crystal defects.
The incorporation of these elements enhances the internal quantum efficiency of the phosphor, leading to improved luminous efficiency and reduced absorption of excitation light, resulting in superior performance.
Smart Images

Figure 2024177565000001 
Figure 2024177565000002 
Figure 2024177565000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a europium-activated β-sialon phosphor and a light-emitting device. [Background technology]
[0002] Oxynitride phosphors are known as phosphors that exhibit little decrease in luminance with increasing temperature and have excellent durability. Among oxynitride phosphors, europium-activated β-sialon is known as a green phosphor that can be excited by ultraviolet light, visible light, or the like.
[0003] The β-SiAlON phosphor can be obtained by, for example, heating a raw material mixture containing silicon nitride powder, aluminum nitride powder, and europium oxide powder under a nitrogen atmosphere. In the study of practical application of the β-SiAlON phosphor, there are also studies on further improving the luminous efficiency (for example, Patent Document 1).
[0004] Also, studies have been made to improve the luminance of light emitted. For example, Patent Document 2 describes a method for producing a β-sialon phosphor, which includes a first heat treatment step of heat-treating a mixture containing an aluminum compound, a first europium compound, and silicon nitride to obtain a first heat-treated product, and a second heat treatment step of heat-treating the first heat-treated product and a second europium compound in a rare gas atmosphere to obtain a second heat-treated product. Patent Document 3 also proposes a method for producing a β-sialon phosphor, which includes a firing step of firing a raw material mixture of a β-sialon phosphor at a temperature of 1820°C to 2200°C in a nitrogen atmosphere to obtain a fired product, and an annealing step of annealing the fired product at a temperature of 1100°C or higher in a reducing atmosphere. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2013-519750 [Patent Document 2] JP 2017-002278 A [Patent Document 3] International Publication No. 2010 / 143590 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present disclosure is to provide a europium-activated β-sialon phosphor having excellent internal quantum efficiency. [Means for solving the problem]
[0007] One aspect of the present disclosure provides a europium-activated β-sialon phosphor containing at least one element selected from the group consisting of yttrium, titanium, and gadolinium, the total content of the at least one element being more than 0 ppm and less than 1000 ppm.
[0008] The europium-activated β-sialon has excellent internal quantum efficiency because it contains the above-mentioned elements in the specified amounts.
[0009] The at least one element may be yttrium, the at least one element may be titanium, or the at least one element may be yttrium and titanium. The europium-activated β-sialon phosphor has a higher internal quantum efficiency by containing a predetermined amount of yttrium or titanium.
[0010] The at least one element may contain at least one of yttrium and titanium, and the total content of the yttrium and titanium may be 0.1 to 500 ppm. When the total content of yttrium and titanium is within the above range, crystal defects in the phosphor can be further reduced, resulting in superior internal quantum efficiency.
[0011] The at least one element may contain at least one of yttrium and titanium, and the absorptance for excitation light with a wavelength of 600 nm may be 5% or less.
[0012] The at least one element may be gadolinium. The europium-activated β-sialon phosphor contains a predetermined amount of gadolinium, and therefore has superior internal quantum efficiency.
[0013] The gadolinium content may be 0.1 to 300 ppm. When the gadolinium content is within the above range, crystal defects in the phosphor can be further reduced, resulting in superior internal quantum efficiency.
[0014] The europium-activated β-sialon phosphor in which the at least one element is gadolinium may have an absorptance of 6% or less for excitation light with a wavelength of 600 nm.
[0015] One aspect of the present disclosure provides a europium-activated β-sialon phosphor that contains alkaline earth metal elements, in which the total content of the alkaline earth metal elements is more than 0 ppm and less than 1000 ppm.
[0016] The europium-activated β-sialon phosphor has excellent internal quantum efficiency because it contains a predetermined amount of alkaline earth metal element.
[0017] The alkaline earth metal element may be magnesium or strontium. By including magnesium or strontium, crystal defects in the phosphor can be further reduced, resulting in superior internal quantum efficiency.
[0018] The total content of the alkaline earth metal elements may be 0.1 to 500 ppm. When the content of the alkaline earth metal elements is within the above range, crystal defects in the phosphor can be further reduced, resulting in superior internal quantum efficiency.
[0019] The alkaline earth metal element-containing europium-activated β-sialon phosphor may have an absorptance of 7% or less for excitation light with a wavelength of 600 nm.
[0020] One aspect of the present disclosure provides a light emitting device including a light emitting element that emits primary light, and a wavelength converter that absorbs a portion of the primary light and emits secondary light having a wavelength longer than that of the primary light, wherein the wavelength converter includes the above-mentioned europium-activated β-sialon phosphor.
[0021] The light emitting device has excellent luminous efficiency because it contains the europium-activated β-sialon phosphor as a wavelength converter. Effect of the Invention
[0022] According to the present disclosure, it is possible to provide a europium-activated β-sialon phosphor having excellent internal quantum efficiency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0024] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In this specification, the "steps" may be steps independent of each other or steps performed simultaneously.
[0025] One embodiment of the europium-activated β-sialon phosphor contains at least one element selected from the group consisting of yttrium, titanium, and gadolinium. The europium-activated β-sialon phosphor may contain, for example, one or two elements selected from the group consisting of yttrium, titanium, and gadolinium among the above elements, and may contain one element selected from the group consisting of yttrium, titanium, and gadolinium. The above at least one element may be, for example, yttrium, may be titanium, or may be gadolinium. When the europium-activated β-sialon phosphor contains two of the above elements, the above at least one element may be yttrium and titanium. For example, the europium-activated β-sialon phosphor may be a phosphor containing yttrium, may be a phosphor containing titanium, or may be a phosphor containing yttrium and titanium. That is, the europium-activated β-sialon phosphor may contain at least one of yttrium and titanium. The europium-activated β-sialon phosphor may also be a phosphor containing gadolinium.
[0026] The above europium-activated β-sialon phosphor may contain β-sialon as a main crystal or may consist of β-sialon. The europium-activated β-sialon phosphor may contain heterogeneous phases as long as the gist of the present disclosure is not impaired. The europium-activated β-sialon phosphor contains Si 6-Z Al Z O Z N 8-Z :Eu may have a composition represented by the compositional formula. In the above compositional formula, z may be 0.0 < z ≤ 4.2 or may be 0.0 < z ≤ 0.5. The composition of the europium-activated β-sialon phosphor can be adjusted by changing the components and composition ratios of the raw material composition when manufacturing the phosphor.
[0027] In the composition of the europium-activated β-sialon phosphor according to this embodiment, the contents of nitrogen atoms (N) and oxygen atoms (O) can be quantified using an oxygen / nitrogen analyzer, and the contents of europium (Eu), silicon (Si), aluminum (Al), yttrium (Y), titanium (Ti), and gadolinium (Gd) can be confirmed by quantitative elemental analysis using an ICP optical emission spectrometer.
[0028] In the europium-activated β-sialon phosphor, the total content of the at least one element is more than 0 ppm and less than 1000 ppm. The total content of the at least one element can be adjusted depending on the type of the element contained in the europium-activated β-sialon phosphor.
[0029] The total content of yttrium and titanium is more than 0 ppm and less than 1000 ppm based on the total amount of the europium-activated β-sialon phosphor. The europium-activated β-sialon phosphor according to this embodiment has a superior internal quantum efficiency, and the inventors presume that the reason for this effect is as follows. That is, in the europium-activated β-sialon phosphor according to this embodiment, defects in the phosphor that occur during the production of the phosphor are filled with yttrium or titanium ions, thereby reducing defects, and the phosphor has a superior internal quantum efficiency.
[0030] The lower limit of the yttrium content may be, for example, 0.1 ppm or more, or 0.2 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. When the lower limit of the yttrium content is within the above range, the internal quantum efficiency of the europium-activated β-sialon phosphor can be further improved. The upper limit of the yttrium content may be, for example, 800 ppm or less, 600 ppm or less, or 500 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. When the upper limit of the yttrium content is within the above range, the generation of a different phase derived from the excessively added yttrium can be suppressed, and the generation of non-luminescent components can be suppressed, so that the deterioration of the luminescent properties of the europium-activated β-sialon phosphor can be suppressed. The content of yttrium may be adjusted within the above-mentioned range, and may be, for example, 0.1 to 900 ppm, or 0.1 to 500 ppm based on the total amount of the europium-activated β-sialon phosphor.
[0031] The lower limit of the titanium content may be, for example, 0.1 ppm or more, or 0.2 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. When the lower limit of the titanium content is within the above range, the internal quantum efficiency of the europium-activated β-sialon phosphor can be further improved. The upper limit of the titanium content may be, for example, 800 ppm or less, 600 ppm or less, or 500 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. When the upper limit of the titanium content is within the above range, the generation of a different phase derived from excessively added titanium can be suppressed, and the generation of non-luminescent components can be suppressed, so that the deterioration of the luminescent properties of the europium-activated β-sialon phosphor can be suppressed. The titanium content may be adjusted within the above range, and may be, for example, 0.1 to 900 ppm, or 0.1 to 500 ppm, based on the total amount of the europium-activated β-sialon phosphor.
[0032] The lower limit of the total content of yttrium and titanium may be, for example, 0.1 ppm or more, or 0.2 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. When the lower limit of the total content of yttrium and titanium is within the above range, the internal quantum efficiency of the europium-activated β-sialon phosphor can be further improved. The upper limit of the total content of yttrium and titanium may be, for example, 800 ppm or less, 600 ppm or less, or 500 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. When the upper limit of the total content of yttrium and titanium is within the above range, the generation of heterogeneous phases derived from the excessively added yttrium and titanium elements can be suppressed, and the generation of non-luminescent components can be suppressed, so that the deterioration of the luminescent properties of the europium-activated β-sialon phosphor can be suppressed. The total content of the yttrium and titanium may be adjusted within the above-mentioned range, and may be, for example, 0.1 to 900 ppm, or 0.1 to 500 ppm based on the total amount of the europium-activated β-sialon phosphor.
[0033] The gadolinium content is more than 0 ppm and less than 1000 ppm based on the total amount of the europium-activated β-sialon phosphor. The europium-activated β-sialon phosphor according to this embodiment has a superior internal quantum efficiency, and the inventors presume that the reason for this effect is as follows. That is, in the europium-activated β-sialon phosphor according to this embodiment, defects in the phosphor that occur during the production of the phosphor are filled with gadolinium ions, thereby reducing defects, and the phosphor has a superior internal quantum efficiency.
[0034] The lower limit of the gadolinium content may be, for example, 0.1 ppm or more, or 0.2 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. When the lower limit of the gadolinium content is within the above range, the internal quantum efficiency of the europium-activated β-sialon phosphor can be further improved. The upper limit of the gadolinium content may be, for example, 800 ppm or less, 600 ppm or less, 500 ppm or less, or 300 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. When the upper limit of the gadolinium content is within the above range, the generation of heterogeneous phases derived from excessively added gadolinium can be suppressed, and the generation of non-luminescent components can be suppressed, so that the deterioration of the luminescence characteristics of the europium-activated β-sialon phosphor can be suppressed. The gadolinium content may be adjusted within the above range, and may be, for example, 0.1 to 900 ppm, 0.1 to 500 ppm, or 0.1 to 300 ppm, based on the total amount of the europium-activated β-sialon phosphor.
[0035] Another embodiment of the europium-activated β-sialon phosphor contains an alkaline earth metal element. The europium-activated β-sialon phosphor may contain β-sialon as a main crystal, or may be composed of β-sialon. The europium-activated β-sialon phosphor may contain heterogeneous phases as long as the gist of the present disclosure is not impaired. The europium-activated β-sialon phosphor contains Si 6-Z Al Z O Z N 8-Z :Eu and may have a composition represented by the composition formula. In the above composition formula, z may be 0.0 < z ≤ 4.2, or may be 0.0 < z ≤ 0.5. The composition of the europium-activated β-sialon phosphor can be adjusted by changing the components and composition ratios of the raw material composition when manufacturing the phosphor.
[0036] In the composition of the europium-activated β-sialon phosphor according to this embodiment, the content of alkaline earth metal elements such as magnesium (Mg) and strontium (Sr) can be confirmed by performing quantitative analysis of the elements using an ICP emission spectroscopic analyzer.
[0037] The alkaline earth metal may be any of the group II elements in the periodic table published by IUPAC, and may include, for example, at least one element selected from the group consisting of magnesium, calcium, strontium, and barium, and preferably includes magnesium or strontium.
[0038] The total content of the alkaline earth metal elements is more than 0 ppm and less than 1000 ppm based on the total amount of the europium-activated β-sialon phosphor. The europium-activated β-sialon phosphor according to this embodiment has excellent internal quantum efficiency, and the inventors presume that the reason for such an effect is as follows. That is, in the europium-activated β-sialon phosphor according to this embodiment, defects in the phosphor that occur during the production of the phosphor are filled with ions of elements belonging to alkaline earth metals, thereby reducing defects, and the phosphor has excellent internal quantum efficiency.
[0039] The lower limit of the total content of the alkaline earth metal elements may be, for example, 0.1 ppm or more, or 0.2 ppm or more, based on the total amount of the europium-activated β-sialon phosphor. When the lower limit of the total content of the alkaline earth metal elements is within the above range, the internal quantum efficiency of the europium-activated β-sialon phosphor can be further improved. The upper limit of the total content of the alkaline earth metal elements may be, for example, 800 ppm or less, 600 ppm or less, 500 ppm or less, or 300 ppm or less, based on the total amount of the europium-activated β-sialon phosphor. When the upper limit of the total content of the alkaline earth metal elements is within the above range, the generation of heterogeneous phases derived from the excessively added alkaline earth metal elements can be suppressed, and the generation of non-luminescent components can be suppressed, so that the deterioration of the luminescent properties of the europium-activated β-sialon phosphor can be suppressed. The total content of the alkaline earth metal elements may be adjusted within the above-mentioned range, and may be, for example, 0.1 to 900 ppm, 0.1 to 500 ppm, or 0.1 to 300 ppm based on the total amount of the europium-activated β-sialon phosphor.
[0040] The 50% cumulative diameter (D50) in the volume-based cumulative particle size distribution of the europium-activated β-sialon phosphor according to the present disclosure may be adjusted depending on the use of the phosphor. The 50% cumulative diameter (D50) in the volume-based cumulative particle size distribution of the europium-activated β-sialon phosphor may be, for example, 0.1 to 50 μm, 3 to 40 μm, or 6 to 30 μm. D50 can be controlled, for example, by adjusting the conditions such as the heating temperature and heating time during phosphor production, and by classification.
[0041] In this specification, D50 refers to the particle size when the cumulative value from the small particle size reaches 50% of the total in the volume-based particle size distribution curve measured by the laser diffraction / scattering method. The particle size distribution curve of the phosphor is measured in accordance with the particle size distribution measurement method by the laser diffraction / scattering method described in JIS R 1629:1997 "Method for measuring particle size distribution by the laser diffraction / scattering method for fine ceramic raw materials". A particle size distribution measurement device can be used for the measurement. Specifically, 0.1 g of the phosphor to be measured is first put into 100 mL of ion-exchanged water, a small amount of sodium hexametaphosphate is added, and the measurement sample is dispersed for 3 minutes using an ultrasonic homogenizer. The particle size is measured using a particle size distribution measurement device, and D50 is determined from the obtained particle size distribution. D50 is also called the median diameter and means the average particle size of the target particles. In addition, as a particle size distribution measurement device, for example, "Microtrac MT3300EX II" (product name) manufactured by Microtrac Bell Co., Ltd. can be used. As the ultrasonic homogenizer, for example, "Ultrasonic Homogenizer US-150E" (product name, tip size: φ20, Amplitude: 100%, oscillation frequency: 19.5 KHz, amplitude: approximately 31 μm) manufactured by Nippon Seiki Seisakusho Co., Ltd. can be used.
[0042] The europium-activated β-sialon phosphor according to the present disclosure has a suppressed absorptance for light with a wavelength of 600 nm. The absorption of europium in the phosphor for light with a wavelength of 600 nm is small, and the influence of fluorescence generated by the phosphor is also small at this wavelength. Therefore, when the absorptance for light with a wavelength of 600 nm is high, it is considered that the absorption is due to defects or heterophases that are non-luminescent components. In the europium-activated β-sialon phosphor according to the present disclosure, the absorptance for excitation light with a wavelength of 600 nm can be, for example, 7% or less, 6.8% or less, 6.0% or less, 5.0% or less, 4.8% or less, 4.5% or less, or 4.0% or less. The europium-activated β-sialon phosphor has a suppressed absorption for excitation light with a wavelength of 600 nm, and is less influenced by defects or heterophases that are non-luminescent components, so that it can have a superior internal quantum efficiency.
[0043] When the europium-activated β-sialon phosphor contains at least one of yttrium and titanium, the absorptivity of light with a wavelength of 600 nm can be, for example, 5.0% or less, 4.8% or less, 4.5% or less, or 4.0% or less.When the europium-activated β-sialon phosphor contains gadolinium, the absorptivity of light with a wavelength of 600 nm can be, for example, 6.0% or less, 5.5% or less, or 5% or less.
[0044] When the europium-activated β-sialon phosphor contains an alkaline earth metal element, the absorptance for light with a wavelength of 600 nm can be, for example, 7% or less, 6% or less, or 5% or less.
[0045] The europium-activated β-sialon phosphor according to the present disclosure has excellent internal quantum efficiency, and the internal quantum efficiency can be, for example, more than 80%, 81% or more, 82% or more, 83% or more, or 84% or more.
[0046] In this specification, the light absorptance and internal quantum efficiency refer to the quantum efficiency obtained when the phosphor is excited with near-ultraviolet light having a wavelength of 455 nm, unless otherwise specified. Specifically, the internal quantum efficiency is determined by measuring the efficiency using the method described in the examples of this specification.
[0047] The europium-activated β-sialon phosphor according to the present disclosure can be produced, for example, by the following method. An example of a method for producing a europium-activated β-sialon phosphor may include a firing step of obtaining a fired body containing β-sialon from a raw material composition containing a silicon source, an aluminum source, and a europium source, at least one of which is a nitride, by one or more heat treatments, and an annealing step of obtaining an annealed body from a mixture containing the fired body and at least one of a source of at least one element selected from the group consisting of yttrium, titanium, and gadolinium, or at least one of an alkaline earth metal simple substance and a compound having an alkaline earth metal element as a constituent element, by one or more annealing treatments under an atmosphere containing at least one selected from the group consisting of a rare gas, a reducing gas, and an inert gas. Examples of the supply source of at least one element selected from the group consisting of yttrium, titanium, and gadolinium include at least one selected from the group consisting of yttrium alone, titanium alone, a compound having yttrium as a constituent element, and a compound having titanium as a constituent element, as well as at least one of gadolinium alone or a compound having gadolinium as a constituent element, etc. Examples of this will be described below.
[0048] The raw material composition includes a compound having an element that is a constituent element of europium-activated β-sialon, and contains at least a silicon source, an aluminum source, and a europium source. In the raw material composition, at least one of the silicon source, the aluminum source, and the europium source is a nitride. The nitride contains nitrogen that is a constituent element of europium-activated β-sialon, and therefore is also a nitrogen source.
[0049] The silicon source means a compound or simple substance having silicon as a constituent element, the aluminum source means a compound or simple substance having aluminum as a constituent element, and the europium source means a compound or simple substance having europium as a constituent element. In this specification, a compound having silicon as a constituent element is also called a silicon compound, a compound having aluminum as a constituent element is also called an aluminum compound, and a compound having europium as a constituent element is also called a europium compound.
[0050] The silicon compound, the aluminum compound, and the europium compound may each be any one of a nitride, an oxide, an oxynitride, and a hydroxide. The raw material composition may further contain β-sialon or europium-activated β-sialon. Here, the β-sialon or europium-activated β-sialon is a material to be an aggregate or a core.
[0051] Examples of silicon compounds include silicon nitride (Si3N4) and silicon oxide (SiO2). It is preferable to use silicon nitride having a high α fraction. The α fraction of silicon nitride may be, for example, 80 mass% or more, 90 mass% or more, or 95 mass% or more. When the α fraction of silicon nitride is within the above range, primary particle growth can be promoted. It is preferable to use silicon nitride having a small oxygen content. The oxygen content of silicon nitride may be, for example, 3.0 mass% or less, or 1.3 mass% or less. When the oxygen content of silicon nitride is within the above range, the occurrence of defects in the crystal of β-sialon can be suppressed.
[0052] Examples of aluminum compounds include aluminum nitride (AlN), aluminum oxide (Al2O3), and aluminum hydroxide (Al(OH)3).
[0053] Examples of europium compounds include europium oxide (europium oxide), europium nitride (europium nitride), and europium halides. Examples of europium halides include europium fluoride, europium chloride, europium bromide, and europium iodide. The europium compound preferably includes europium oxide. The valence of europium in the europium compound may be divalent or trivalent, and is preferably divalent.
[0054] The raw material mixture can be prepared by weighing and mixing each compound. A dry mixing method or a wet mixing method may be used for mixing. The dry mixing method may be, for example, a method in which each component is mixed using a V-type mixer or the like. The wet mixing method may be, for example, a method in which a solvent or dispersion medium such as water is added to prepare a solution or slurry, the components are mixed, and then the solvent or dispersion medium is removed.
[0055] The heating temperature in the firing step may be, for example, 1800 to 2500°C, 1800 to 2400°C, 1850 to 2100°C, 1900 to 2100°C, 1900 to 2050°C, or 1920 to 2050°C. By setting the heating temperature in the firing step to 1800°C or higher, the particle growth of β-sialon can be promoted and the amount of europium dissolved in solid solution can be made more sufficient. By setting the heating temperature in the firing step to 2500°C or lower, the decomposition of the crystal of β-sialon can be sufficiently suppressed.
[0056] The heating time in the firing step is preferably long from the viewpoint of promoting the growth of primary particles of β-sialon. However, if the heating time is too long, crystal defects may increase, so the heating time may be, for example, 1 to 30 hours, 3 to 25 hours, or 5 to 20 hours.
[0057] The raw material mixture may be heated in a nitrogen atmosphere in the firing step. By heating under conditions of high nitrogen partial pressure, decomposition of silicon nitride at high temperatures can be suppressed. Furthermore, by treating at high temperatures, particle growth can be promoted. The raw material mixture may be heated under pressure in the firing step. The pressure may be, for example, 0.01 to 200 MPaG, 0.02 to 200 MPaG, 0.1 to 200 MPaG, 0.1 to 100 MPaG, 0.1 to 50 MPaG, 0.1 to 15 MPaG, or 0.1 to 5 MPaG.
[0058] The number of times of heat treatment in the firing step may be 1, but may be, for example, 2 or more, such as 2 to 5 or 2 to 4. By performing heat treatment multiple times, a europium-activated β-sialon phosphor having superior emission intensity can be obtained.
[0059] In the firing step, one or more heat treatments are performed. When multiple heat treatments are performed, they are successively referred to as the first heat treatment, the second heat treatment, etc., and each heat treatment step may be successively referred to as the first firing step, the second firing step, etc. For example, when the above-mentioned manufacturing method performs two heat treatments in the firing step, the firing step is also said to include a step of first heating a raw material composition containing a nitride to obtain a first heat-treated body, and a second heating the first heat-treated body to obtain a second heat-treated body. In this case, the second heat-treated body corresponds to a fired body containing β-sialon. Before performing multiple heat treatments, the silicon source, the aluminum source, and the europium source may be further mixed and heat-treated.
[0060] When the firing step includes two or more heating processes, the heating temperature, heating time, heating atmosphere, and heating pressure of the first firing step can be the same as those of the above-mentioned heating step. The heating temperature, heating time, heating atmosphere, and heating pressure of the second firing step and thereafter may be the same as or different from those of the first firing step. However, even if the heating temperature, heating time, heating atmosphere, and heating pressure of the second firing step and thereafter are different from those of the first firing step, they are within the range of conditions shown for the above-mentioned heating step.
[0061] The sintered body obtained in the sintering step has β-SiAlON crystals, and is a solid solution in which an element serving as a luminescence center is dissolved in a part of the crystals, and can emit fluorescence by itself. The sintered body obtained in the sintering step may be in a lump shape, and the particle size may be adjusted by crushing or the like prior to the annealing step.
[0062] Next, an annealing step is performed. The annealing step in the manufacturing method of this example means a step of obtaining an annealed body from a mixture containing the sintered body obtained in the above-mentioned sintering step and a source of at least one element selected from the group consisting of yttrium, titanium, and gadolinium, or at least one of an alkaline earth metal element and a compound having an alkaline earth metal element as a constituent element. The above-mentioned step may be, for example, a step of annealing a mixture containing the sintered body obtained in the above-mentioned sintering step and at least one selected from the group consisting of an yttrium element, a titanium element, a compound having yttrium as a constituent element, and a compound having titanium as a constituent element, or a step of annealing a mixture containing the sintered body obtained in the above-mentioned sintering step and at least one of a gadolinium element or a compound having gadolinium as a constituent element, or a step of annealing a mixture containing the sintered body obtained in the above-mentioned sintering step and at least one of an alkaline earth metal element and a compound having an alkaline earth metal element as a constituent element. In the annealing step, an annealed body is obtained from the mixture by one or more heat treatments.
[0063] The compound having yttrium as a constituent element and the compound having titanium as a constituent element may be, for example, an oxide, a nitride, a hydroxide, etc., but is preferably an oxide. The compound having yttrium as a constituent element and the compound having titanium as a constituent element may be, for example, yttrium oxide (Y2O3) and titanium oxide (Ti2O3).
[0064] The total amount of the yttrium element, the titanium element, the compound having yttrium as a constituent element, and the compound having titanium as a constituent element may be, for example, 0.01 to 4 mass%, 0.05 to 3 mass%, or 0.1 to 3 mass% based on the total amount of the mixture. By making the amount 0.01 mass% or more, at least one of yttrium and titanium can be more easily introduced into the phosphor, and the internal quantum efficiency of the obtained europium-activated β-sialon phosphor can be further improved. By making the amount 4 mass% or less, the deterioration of the luminescence characteristics of the obtained europium-activated β-sialon phosphor can be suppressed.
[0065] The compound having gadolinium as a constituent element may be, for example, an oxide, a nitride, a hydroxide, etc., but is preferably an oxide. The compound having gadolinium as a constituent element may be, for example, gadolinium oxide (Gd2O3).
[0066] The total amount of the gadolinium simple substance and the compound having gadolinium as a constituent element may be, for example, 0.01 to 4 mass%, 0.05 to 3 mass%, or 0.1 to 3 mass% based on the total amount of the mixture. By making the total amount of the gadolinium simple substance and the compound having gadolinium as a constituent element 0.01 mass% or more, it becomes easy to introduce gadolinium into the phosphor, and the internal quantum efficiency of the obtained europium-activated β-type sialon phosphor can be further improved. By making the total amount of the gadolinium simple substance and the compound having gadolinium as a constituent element 4 mass% or less, a heterogeneous phase derived from excessively added gadolinium can be suppressed, and the deterioration of the luminescence characteristics of the obtained europium-activated β-type sialon phosphor can be suppressed.
[0067] The compound having an alkaline earth metal element as a constituent element may be, for example, an oxide, a carbonate, a nitride, a hydroxide, etc., but is preferably an oxide or a carbonate. The alkaline earth metal element may be an alkaline earth metal element exemplified as a constituent component of the europium-activated β-SiAlON phosphor. The compound having an alkaline earth metal element as a constituent element may be, for example, magnesium oxide (MgO), strontium carbonate (SrCO3), strontium nitride (Sr2N3), strontium oxide (SrO), etc.
[0068] The total amount of the alkaline earth metal and the compound having an alkaline earth metal element as a constituent element may be, for example, 0.01 to 4 mass%, 0.05 to 3 mass%, 0.1 to 3 mass%, or 0.1 to 1.5 mass% based on the total amount of the mixture. By making the total amount of the alkaline earth metal and the compound having an alkaline earth metal element as a constituent element 0.01 mass% or more, it becomes easy to introduce the alkaline earth metal element into the phosphor, and the internal quantum efficiency of the obtained europium-activated β-type sialon phosphor can be further improved. By making the total amount of the alkaline earth metal and the compound having an alkaline earth metal element as a constituent element 4 mass% or less, a heterogeneous phase derived from the excessively added alkaline earth metal element can be suppressed, and the deterioration of the luminescence characteristics of the obtained europium-activated β-type sialon phosphor can be suppressed.
[0069] The annealing step is performed in an atmosphere containing at least one gas selected from the group consisting of a rare gas, a reducing gas, and an inert gas. By performing the annealing treatment in an atmosphere containing a rare gas, a reducing gas, or an inert gas, the proportion of divalent europium in the europium in the solid solution can be increased.
[0070] The rare gas may contain, for example, argon, helium, etc., may contain argon, or may consist of argon. The reducing gas may contain, for example, ammonia, hydrocarbon, carbon monoxide, hydrogen, etc., may contain hydrogen, or may consist of hydrogen. The inert gas may contain, for example, nitrogen, etc., or may consist of nitrogen. The atmosphere of the annealing step may be a mixed gas of two or more of the rare gas, the reducing gas, and the inert gas. When the atmosphere of the annealing step is the mixed gas, the content of the reducing gas may be, for example, 1 to 50 volume % or 4 to 20 volume % based on the total volume of the mixed gas. The content of the inert gas may be, for example, 1 to 50 volume % or 4 to 20 volume % based on the total volume of the mixed gas.
[0071] The pressure during the annealing treatment may be the same as that during the firing step, but is preferably lower than the pressure condition during the firing step, and more preferably atmospheric pressure.
[0072] The temperature of the annealing treatment needs to be set lower than the heating temperature in the sintering process. The upper limit of the annealing treatment temperature may be, for example, 1700°C or lower, or 1680°C or lower. By setting the upper limit of the annealing treatment temperature within the above range, further particle growth in the sintered body can be suppressed from occurring, such as aggregation between solid solutions and formation of secondary particles, resulting in coarsening of the particles. The lower limit of the annealing treatment temperature may be, for example, 1000°C or higher, 1100°C or higher, 1200°C or higher, 1300°C or higher, or 1400°C or higher. By setting the lower limit of the annealing treatment temperature within the above range, the crystal defect density of the β-type sialon contained in the annealed body can be reduced, and the internal quantum efficiency can be further improved. The annealing treatment temperature can be adjusted within the above range, and may be, for example, 1000 to 1700°C, or 1100 to 1680°C.
[0073] The heating time in the annealing treatment may be, for example, 1 to 30 hours, 2 to 25 hours, or 3 to 20 hours, from the viewpoint of further reducing crystal defects in the phosphor contained in the annealed body.
[0074] In the annealing step, one or more annealing treatments are performed. When multiple annealing treatments are performed, they are successively referred to as the first annealing treatment, the second annealing treatment, etc., and the steps of performing each annealing treatment may be successively referred to as the first annealing treatment, the second annealing treatment, etc. For example, when the above-mentioned manufacturing method performs two annealing treatments in the annealing step, the annealing step is also said to include a step of performing a first annealing treatment on the fired body to obtain a first annealed body, and a second annealing treatment on the first annealed body to obtain a second annealed body. In this case, the second annealed body corresponds to the above-mentioned annealed body.
[0075] When the annealing step includes two or more annealing steps, the annealing temperature, heating time, and heating pressure of the first annealing step can be the same as the annealing temperature, heating time, and heating pressure of the annealing step described above. The annealing temperature, heating time, and heating pressure of the second annealing step and subsequent steps may be the same as or different from the first annealing step. However, even if the annealing temperature, heating time, and heating pressure of the second annealing step and subsequent steps are different from those of the first annealing step, they are within the range of conditions shown for the annealing step described above.
[0076] The number of times of annealing treatment in the annealing step may be 1, but may also be, for example, 2 or more, such as 2 to 5 or 2 to 4. By performing annealing treatment multiple times, it is possible to reduce the crystal defect density of the β-SiAlON contained in the annealed body, and to obtain a europium-activated β-SiAlON phosphor with better internal quantum efficiency.
[0077] When the annealing treatment is performed multiple times in the annealing step, at least one of a source of at least one element selected from the group consisting of yttrium, titanium, and gadolinium (e.g., the above-mentioned yttrium alone, titanium alone, a compound having yttrium as a constituent element, and a compound having titanium as a constituent element, or gadolinium alone and a compound having gadolinium as a constituent element, etc.) or an alkaline earth metal alone and a compound having an alkaline earth metal element as a constituent element may be mixed all at once in the first annealing step, or may be mixed in portions over multiple annealing steps, but is preferably mixed all at once in the first annealing step. In addition, when these compounds are mixed in portions, the description regarding the total amount of at least one of the above-mentioned sources of at least one element selected from the group consisting of yttrium, titanium, and gadolinium, or the alkaline earth metal alone, and the compound having an alkaline earth metal element as a constituent element, should be read and applied as the total amount of at least one of the above-mentioned sources of at least one element selected from the group consisting of yttrium, titanium, and gadolinium, or the alkaline earth metal alone, and the compound having an alkaline earth metal element as a constituent element, which are mixed in multiple annealing steps.
[0078] The method for producing a europium-activated β-sialon phosphor may include other steps in addition to the firing step and the annealing step. The other steps may include, for example, a step of treating the annealed body obtained in the annealing step with at least one of an acid and an alkali, a classification step of adjusting the particle size of the annealed body or the annealed body that has been subjected to an acid treatment or the like, etc. The step of treating the annealed body with an acid is called an acid treatment step, and the step of treating the annealed body with an alkali is called an alkali treatment step.
[0079] The acid treatment step or alkali treatment step can, for example, further reduce the crystal defect density in the phosphor contained in the annealed body, remove silicon present on the surface of the solid solution produced by thermal decomposition of β-sialon, and remove AlN polytypoid, which is a pseudo-polymorph of aluminum nitride (AlN) produced as a by-product during preparation of the first fired body. The acid can include, for example, hydrofluoric acid and nitric acid. The acid can be a mixed acid of hydrofluoric acid and nitric acid. The alkali can include, for example, sodium hydroxide.
[0080] The classification step may be performed by, for example, either a wet classification method or a dry classification method. Examples of the wet classification include an elutriation classification method in which the annealed body is added to a mixed solvent containing ion-exchanged water and a dispersant (e.g., sodium hexametaphosphate, etc.) or a mixed solvent containing ion-exchanged water and ammonia water, stirred, and then allowed to stand to remove particles with a small particle size.
[0081] The europium-activated β-sialon phosphor according to the present disclosure may be used alone or in combination with other phosphors. The europium-activated β-sialon phosphor according to the present disclosure has excellent internal quantum efficiency, and therefore can be suitably used in light-emitting devices such as LEDs. The phosphor may be dispersed in a cured resin for use. The cured resin is not particularly limited, and may be, for example, a resin used as a sealing resin for light-emitting devices.
[0082] One embodiment of the light emitting device is a light emitting device including a light emitting element that emits primary light, and a wavelength converter that absorbs a part of the primary light and emits secondary light having a wavelength longer than that of the primary light. The wavelength converter includes the europium-activated β-sialon phosphor described above. The light emitting element that emits the primary light may be, for example, an InGaN blue LED. The light emitting element and the wavelength converter may be dispersed in a sealing resin or the like.
[0083] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0084] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.
[0085] (Comparative example I-1) [Preparation of europium-activated β-SiAlON phosphor] Each raw material was weighed and placed in a container so that silicon nitride (Si3N4) was 96.0 mass%, aluminum nitride (AlN) was 2.8 mass%, aluminum oxide (Al2O3) was 0.5 mass%, and europium oxide (Eu2O3) was 0.7 mass%, and mixed using a V-type mixer (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.) to obtain a mixture. The obtained mixture was passed through a sieve with a mesh size of 250 μm to remove aggregates, thereby obtaining a raw material composition. The aggregates that did not pass through the sieve were pulverized, and the particle size was adjusted so that they would pass through the sieve.
[0086] 200 g of the raw material composition prepared as described above was weighed out and placed in a cylindrical boron nitride container with a lid (a molded product made by Denka Co., Ltd., mainly composed of boron nitride (product name: Denka Boron Nitride N-1), inner diameter: 10 cm, height: 10 cm). The container was then placed in an electric furnace equipped with a carbon heater, heated to 2020°C under a nitrogen gas atmosphere (pressure: 0.90 MPaG), and heated at a heating temperature of 2020°C for 8 hours (firing process). After heating, the sample that had become loosely aggregated lumps in the container was taken in a mortar and crushed. After crushing, the sample was passed through a sieve with an opening of 250 μm to obtain a powdered first fired body.
[0087] Next, the first fired body was filled into a cylindrical boron nitride container, and the container was placed in an electric furnace equipped with a carbon heater. The temperature was raised to 1450°C in an argon gas atmosphere (pressure: 0.025 MPaG), and heating was performed at the heating temperature of 1450°C for 3 hours (annealing step). After heating, the lumps of loosely aggregated particles in the container were crushed in a mortar and passed through a 250 μm sieve to obtain a powder.
[0088] Next, the obtained powder was added to a mixed acid of hydrofluoric acid (concentration: 50% by mass) and nitric acid (concentration: 70% by mass) (hydrofluoric acid and nitric acid were mixed in a volume ratio of 1:1), and acid treatment was performed for 30 minutes while stirring at a temperature of 75°C. After the acid treatment, the stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder refined by the acid treatment were removed. Then, distilled water was further added and the mixture was stirred again. The stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder were removed. This operation was repeated until the pH of the aqueous solution was 8 or less and the supernatant was transparent, and the obtained precipitate was filtered and dried to obtain a europium-activated β-type Sialon phosphor.
[0089] (Comparative example I-2) A europium-activated β-type SiAlON phosphor was obtained in the same manner as in Comparative Example I-1, except that the atmosphere in the annealing step was changed from an argon gas atmosphere to a hydrogen gas atmosphere, and the treatment temperature in the annealing step was changed to 1650°C in an electric furnace equipped with a metal heater.
[0090] (Example I-1) In the annealing step, the mixture was adjusted so that the amount of yttrium oxide was 0.1 mass% relative to the total amount of the first fired body and yttrium oxide (100 mass%), and then heated under a hydrogen gas atmosphere. In the same manner as in Comparative Example I-2, a europium-activated β-type SiAlON phosphor was obtained.
[0091] (Example I-2) A europium-activated β-sialon phosphor was obtained in the same manner as in Example I-1, except that the blending amount of yttrium oxide was changed to 0.5 mass %.
[0092] (Example I-3) A europium-activated β-sialon phosphor was obtained in the same manner as in Example I-1, except that the blending amount of yttrium oxide was changed to 1 mass %.
[0093] (Comparative example I-3) A europium-activated β-sialon phosphor was obtained in the same manner as in Example I-1, except that the blending amount of yttrium oxide was changed to 5 mass %.
[0094] (Example I-4) In the annealing step, the mixture was adjusted so that the amount of yttrium oxide was 0.5 mass% relative to the total amount of the first fired body and yttrium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example I-1, a europium-activated β-type SiAlON phosphor was obtained.
[0095] (Example I-5) In the annealing step, the mixture was adjusted so that the amount of titanium oxide was 0.1 mass% relative to 100 mass% of the total amount of the first fired body and titanium oxide, and then heated under an argon gas atmosphere. In the same manner as in Comparative Example I-1, a europium-activated β-type SiAlON phosphor was obtained.
[0096] (Example I-6) A europium-activated β-sialon phosphor was obtained in the same manner as in Example I-5, except that the blending amount of titanium oxide was changed to 0.5 mass %.
[0097] (Example I-7) A europium-activated β-sialon phosphor was obtained in the same manner as in Example I-5, except that the blending amount of titanium oxide was changed to 1 mass %.
[0098] (Comparative example I-4) A europium-activated β-type Sialon phosphor was obtained in the same manner as in Example I-5, except that the blending amount of titanium oxide was changed to 5 mass %.
[0099] (Comparative example I-5) In the annealing step, the mixture was adjusted so that the amount of zirconium oxide was 0.1 mass% relative to the total amount of the first fired body and zirconium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example I-1, a europium-activated β-type SiAlON phosphor was obtained.
[0100] (Comparative example I-6) A europium-activated β-type Sialon phosphor was obtained in the same manner as in Comparative Example I-5, except that the amount of zirconium oxide was changed to 0.5 mass %.
[0101] (Comparative example I-7) In the annealing step, the mixture was adjusted so that the amount of zinc oxide was 0.1 mass% relative to 100 mass% of the total amount of the first fired body and zinc oxide, and then heated under an argon gas atmosphere. In the same manner as in Comparative Example I-1, a europium-activated β-type SiAlON phosphor was obtained.
[0102] (Comparative example I-8) A europium-activated β-type Sialon phosphor was obtained in the same manner as in Comparative Example I-7, except that the amount of zinc oxide was changed to 0.5 mass %.
[0103] (Comparative Example I-9) A standard sample of β-type Sialon phosphor (manufactured by Sialon Corporation, NIMS Standard Green lot No. NSG1301) was used as the phosphor of Comparative Example I-9.
[0104] <Measurement of the content of yttrium, titanium, zirconium and zinc> For each of the europium-activated β-sialon phosphors prepared in Examples I-1 to I-7 and Comparative Examples I-1 to I-8, the contents of yttrium, titanium, zirconium and zinc were measured as follows. The results are shown in Table 1.
[0105] <Content of yttrium, titanium, zirconium and zinc> The contents of yttrium, titanium, zirconium and zinc in the europium-activated β-sialon phosphor were measured by the following procedure. The phosphor was dissolved by the pressurized acid decomposition method to prepare a sample solution. The obtained sample solution was subjected to quantitative elemental analysis using an ICP emission spectrometer (manufactured by Rigaku Corporation, product name: CIROS-120) to measure the contents. The detection limits of yttrium (Y), titanium (Ti), zirconium (Zr) and zinc (Zn) were each 100 ppb.
[0106] [Evaluation of europium-activated β-type sialon phosphor] The absorptivity, internal quantum efficiency, external quantum efficiency, and chromaticity X of each of the europium-activated β-sialon phosphors prepared in Examples I-1 to I-7 and Comparative Examples I-1 to I-9 when irradiated with an excitation light having a wavelength of 455 nm, as well as the absorptivity when irradiated with an excitation light having a wavelength of 600 nm, were evaluated by the methods described below. The results are shown in Table 1.
[0107] <Absorptivity, Internal Quantum Efficiency, and External Quantum Efficiency> The absorptance (excitation light absorptance), internal quantum efficiency, and external quantum efficiency of the phosphor when irradiated with excitation light of 455 nm wavelength were calculated by the following procedure. First, the phosphor to be measured was filled in a concave cell so that the surface was smooth, and the cell was attached to the opening of an integrating sphere. Monochromatic light having a wavelength of 455 nm was split from a Xe lamp, which is a light emission source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The monochromatic light, which is the excitation light, was irradiated onto the phosphor to be measured, and the fluorescence spectrum was measured. A spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., product name: MCPD-7000) was used for the measurement.
[0108] From the obtained fluorescence spectrum data, the emission intensity of the phosphor was determined. Also, from the obtained fluorescence spectrum data, the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. Also, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm.
[0109] From the above calculation results, the absorptance of the 455 nm excitation light, the internal quantum efficiency, and the external quantum efficiency of the phosphor to be measured were calculated based on the following formulas. Absorption rate of 455 nm excitation light = ((Qex-Qref) / Qex) x 100 Internal quantum efficiency = (Qem / (Qex-Qref)) x 100 External quantum efficiency = (Qem / Qex) x 100 From the above formula, the relationship between the external quantum efficiency, the absorptance of 455 nm excitation light, and the internal quantum efficiency can be expressed as follows: External quantum efficiency = 455 nm light absorptance × internal quantum efficiency
[0110] <Chromaticity X> The chromaticity X was obtained by calculating the CIE chromaticity coordinate x value (chromaticity X) in the XYZ color system defined in JIS Z8781-3:2016 from the spectral data in the wavelength range of 465 to 780 nm of the fluorescence spectrum in accordance with JIS Z8724:2015.
[0111] <600nm light absorption rate> A standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was set at the side opening of the integrating sphere. Monochromatic light separated into wavelengths of 600 nm from a light emission source (Xe lamp) was introduced into this integrating sphere via an optical fiber, and the reflected light spectrum was measured with a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). At that time, the number of incident light photons (Qex(600)) was calculated from the spectrum in the wavelength range of 590 to 610 nm.
[0112] Next, the concave cell was filled with β-SiAlON phosphor so that the surface was smooth, and then it was set in the opening of the integrating sphere. Monochromatic light with a wavelength of 600 nm was irradiated, and the incident reflected light spectrum was measured with a spectrophotometer. The incident reflected light photon count (Qref(600)) was calculated from the obtained spectrum data. The incident reflected light photon count (Qref(600)) was calculated in the same wavelength range as the incident light photon count (Qex(600)). The 600 nm light absorptance was calculated from the obtained two types of photon counts based on the following formula. 600 nm light absorption rate = ((Qex(600)-Qref(600)) / Qex(600)) x 100
[0113] The measured values of the absorptance, internal quantum efficiency, external quantum efficiency, and chromaticity X of the phosphor may vary when the manufacturer of the measuring device, the production lot number, etc. are changed. Therefore, the values measured by the measuring method described in this specification are adopted as the various measured values. However, when the manufacturer of the measuring device, the production lot number, etc. are changed, each measured value can be corrected by using the measured value of the standard sample of the β-type Sialon phosphor described above as the reference value. As the standard sample for obtaining the reference value, the standard sample of the β-type Sialon phosphor listed above as Comparative Example I-9 can be used.
[0114] [Table 1]
[0115] (Comparative Example II-1) [Preparation of europium-activated β-SiAlON phosphor] Each raw material was weighed and placed in a container so that silicon nitride (Si3N4) was 96.0 mass%, aluminum nitride (AlN) was 2.8 mass%, aluminum oxide (Al2O3) was 0.5 mass%, and europium oxide (Eu2O3) was 0.7 mass%, and mixed using a V-type mixer (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.) to obtain a mixture. The obtained mixture was passed through a sieve with a mesh size of 250 μm to remove aggregates, thereby obtaining a raw material composition. The aggregates that did not pass through the sieve were pulverized, and the particle size was adjusted so that they would pass through the sieve.
[0116] 200 g of the raw material composition prepared as described above was weighed out and placed in a cylindrical boron nitride container with a lid (a molded product made by Denka Co., Ltd., mainly composed of boron nitride (product name: Denka Boron Nitride N-1), inner diameter: 10 cm, height: 10 cm). The container was then placed in an electric furnace equipped with a carbon heater, heated to 2020°C under a nitrogen gas atmosphere (pressure: 0.90 MPaG), and heated at a heating temperature of 2020°C for 8 hours (firing process). After heating, the sample that had become loosely aggregated lumps in the container was taken in a mortar and crushed. After crushing, the sample was passed through a sieve with an opening of 250 μm to obtain a powdered first fired body.
[0117] Next, the first fired body was filled into a cylindrical boron nitride container, and the container was placed in an electric furnace equipped with a carbon heater. The temperature was raised to 1450°C in an argon gas atmosphere (pressure: 0.025 MPaG), and heating was performed at the heating temperature of 1450°C for 3 hours (annealing step). After heating, the lumps of loosely aggregated particles in the container were crushed in a mortar and passed through a 250 μm sieve to obtain a powder.
[0118] Next, the obtained powder was added to a mixed acid of hydrofluoric acid (concentration: 50% by mass) and nitric acid (concentration: 70% by mass) (hydrofluoric acid and nitric acid were mixed in a volume ratio of 1:1), and acid treatment was performed for 30 minutes while stirring at a temperature of 75°C. After the acid treatment, the stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder refined by the acid treatment were removed. Then, distilled water was further added and the mixture was stirred again. The stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder were removed. This operation was repeated until the pH of the aqueous solution was 8 or less and the supernatant was transparent, and the obtained precipitate was filtered and dried to obtain a europium-activated β-type Sialon phosphor.
[0119] (Comparative Example II-2) In the annealing step, the mixture was adjusted so that the amount of cerium oxide was 0.1 mass% relative to the total amount of the first fired body and cerium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type sialon phosphor was obtained.
[0120] (Comparative Example II-3) In the annealing step, the mixture was adjusted so that the amount of cerium oxide was 0.5 mass% relative to the total amount of the first fired body and cerium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type sialon phosphor was obtained.
[0121] (Comparative Example II-4) In the annealing step, the mixture was adjusted so that the amount of lanthanum oxide was 0.1 mass% relative to the total amount of the first fired body and lanthanum oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type sialon phosphor was obtained.
[0122] (Comparative Example II-5) In the annealing step, the mixture was adjusted so that the amount of lanthanum oxide was 0.5 mass% relative to the total amount of the first fired body and lanthanum oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type sialon phosphor was obtained.
[0123] (Example II-1) In the annealing step, the mixture was adjusted so that the amount of gadolinium oxide was 0.1 mass% relative to the total amount of the first fired body and gadolinium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type SiAlON phosphor was obtained.
[0124] (Example II-2) In the annealing step, the mixture was adjusted so that the amount of gadolinium oxide was 0.5 mass% relative to the total amount of the first fired body and gadolinium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type SiAlON phosphor was obtained.
[0125] (Example II-3) In the annealing step, the mixture was adjusted so that the amount of gadolinium oxide was 1 mass% relative to the total amount of the first fired body and gadolinium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type SiAlON phosphor was obtained.
[0126] (Comparative Example II-6) In the annealing step, the mixture was adjusted so that the amount of gadolinium oxide was 5% by mass relative to the total amount of the first fired body and gadolinium oxide (100% by mass), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example II-1, a europium-activated β-type SiAlON phosphor was obtained.
[0127] (Comparative Example II-7) A standard sample of β-type Sialon phosphor (manufactured by Sialon Corporation, NIMS Standard Green lot No. NSG1301) was used as the phosphor of Comparative Example II-7.
[0128] <Measurement of the content of gadolinium, cerium, and lanthanum> For each of the europium-activated β-sialon phosphors prepared in Examples II-1 to II-3 and Comparative Examples II-1 to II-7, the gadolinium, cerium, and lanthanum contents were measured by the following method. The results are shown in Table 2.
[0129] <Gadolinium, cerium, and lanthanum content> The gadolinium, cerium, and lanthanum contents in the europium-activated β-sialon phosphor were measured by the following procedure. The phosphor was dissolved by a pressure acid decomposition method to prepare a sample solution. The obtained sample solution was subjected to quantitative elemental analysis using an ICP emission spectrometer (manufactured by Rigaku Corporation, product name: CIROS-120). The detection limits for gadolinium (Gd), cerium (Ce), and lanthanum (La) were each 100 ppb.
[0130] [Evaluation of europium-activated β-type sialon phosphor] The absorptivity, internal quantum efficiency, external quantum efficiency, chromaticity X, chromaticity Y, and absorptivity when irradiated with excitation light of 600 nm wavelength were evaluated for each of the europium-activated β-sialon phosphors prepared in Examples II-1 to II-3 and Comparative Examples II-1 to II-7 by the methods described below. The results are shown in Table 2.
[0131] <Absorptivity, Internal Quantum Efficiency, and External Quantum Efficiency> The absorptance (excitation light absorptance), internal quantum efficiency, and external quantum efficiency of the phosphor when irradiated with excitation light of 455 nm wavelength were calculated by the following procedure. First, the phosphor to be measured was filled in a concave cell so that the surface was smooth, and the cell was attached to the opening of an integrating sphere. Monochromatic light having a wavelength of 455 nm was split from a Xe lamp, which is a light emission source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The monochromatic light, which is the excitation light, was irradiated onto the phosphor to be measured, and the fluorescence spectrum was measured. A spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., product name: MCPD-7000) was used for the measurement.
[0132] From the obtained fluorescence spectrum data, the emission intensity of the phosphor was determined. Also, from the obtained fluorescence spectrum data, the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. Also, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm.
[0133] From the above calculation results, the absorptance of the 455 nm excitation light, the internal quantum efficiency, and the external quantum efficiency of the phosphor to be measured were calculated based on the following formulas. Absorption rate of 455 nm excitation light = ((Qex-Qref) / Qex) x 100 Internal quantum efficiency = (Qem / (Qex-Qref)) x 100 External quantum efficiency = (Qem / Qex) x 100 From the above formula, the relationship between the external quantum efficiency, the absorptance of 455 nm excitation light, and the internal quantum efficiency can be expressed as follows: External quantum efficiency = 455 nm light absorptance × internal quantum efficiency
[0134] <Chromaticity X and Y> The chromaticity X and Y were determined from the spectral data in the wavelength range of 465 to 780 nm of the fluorescence spectrum by calculating the x value (chromaticity X) of the CIE chromaticity coordinates and the y value (chromaticity Y) of the CIE chromaticity coordinates in the XYZ color system defined in JIS Z8781-3:2016 in accordance with JIS Z8724:2015.
[0135] <600nm light absorption rate> A standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was set at the side opening of the integrating sphere. Monochromatic light separated into wavelengths of 600 nm from a light emission source (Xe lamp) was introduced into this integrating sphere via an optical fiber, and the reflected light spectrum was measured with a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). At that time, the number of incident light photons (Qex(600)) was calculated from the spectrum in the wavelength range of 590 to 610 nm.
[0136] Next, the concave cell was filled with β-SiAlON phosphor so that the surface was smooth, and then it was set in the opening of the integrating sphere. Monochromatic light with a wavelength of 600 nm was irradiated, and the incident reflected light spectrum was measured with a spectrophotometer. The incident reflected light photon count (Qref(600)) was calculated from the obtained spectrum data. The incident reflected light photon count (Qref(600)) was calculated in the same wavelength range as the incident light photon count (Qex(600)). The 600 nm light absorptance was calculated from the obtained two types of photon counts based on the following formula. 600 nm light absorption rate = ((Qex(600)-Qref(600)) / Qex(600)) x 100
[0137] The measured values of the absorptance, internal quantum efficiency, external quantum efficiency, chromaticity X, and chromaticity Y of the phosphor may vary when the manufacturer of the measuring device, the production lot number, etc. are changed. Therefore, the values measured by the measuring method described in this specification are used as the various measured values. However, when the manufacturer of the measuring device, the production lot number, etc. are changed, each measured value can be corrected by using the measured value of the standard sample of the β-type Sialon phosphor described above as the reference value. As the standard sample for obtaining the reference value, the standard sample of the β-type Sialon phosphor listed above as Comparative Example II-7 can be used.
[0138] [Table 2]
[0139] (Comparative Example III-1) [Preparation of europium-activated β-SiAlON phosphor] Each raw material was weighed and placed in a container so that silicon nitride (Si3N4) was 96.0 mass%, aluminum nitride (AlN) was 2.8 mass%, aluminum oxide (Al2O3) was 0.5 mass%, and europium oxide (Eu2O3) was 0.7 mass%, and mixed using a V-type mixer (manufactured by Tsutsui Rikagaku Kikai Co., Ltd.) to obtain a mixture. The obtained mixture was passed through a sieve with a mesh size of 250 μm to remove aggregates, thereby obtaining a raw material composition. The aggregates that did not pass through the sieve were pulverized, and the particle size was adjusted so that they would pass through the sieve.
[0140] 200 g of the raw material composition prepared as described above was weighed out and placed in a cylindrical boron nitride container with a lid (a molded product made by Denka Co., Ltd., mainly composed of boron nitride (product name: Denka Boron Nitride N-1), inner diameter: 10 cm, height: 10 cm). The container was then placed in an electric furnace equipped with a carbon heater, heated to 2020°C under a nitrogen gas atmosphere (pressure: 0.90 MPaG), and heated at a heating temperature of 2020°C for 8 hours (firing process). After heating, the sample that had become loosely aggregated lumps in the container was taken in a mortar and crushed. After crushing, the sample was passed through a sieve with an opening of 250 μm to obtain a powdered first fired body.
[0141] Next, the first fired body was filled into a cylindrical boron nitride container, and the container was placed in an electric furnace equipped with a carbon heater. The temperature was raised to 1450°C in an argon gas atmosphere (pressure: 0.025 MPaG), and heating was performed at the heating temperature of 1450°C for 3 hours (annealing step). After heating, the lumps of loosely aggregated particles in the container were crushed in a mortar and passed through a 250 μm sieve to obtain a powder.
[0142] Next, the obtained powder was added to a mixed acid of hydrofluoric acid (concentration: 50% by mass) and nitric acid (concentration: 70% by mass) (hydrofluoric acid and nitric acid were mixed in a volume ratio of 1:1), and acid treatment was performed for 30 minutes while stirring at a temperature of 75°C. After the acid treatment, the stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder refined by the acid treatment were removed. Then, distilled water was further added and the mixture was stirred again. The stirring was stopped, the powder was allowed to settle, and the supernatant and fine powder were removed. This operation was repeated until the pH of the aqueous solution was 8 or less and the supernatant was transparent, and the obtained precipitate was filtered and dried to obtain a europium-activated β-type Sialon phosphor.
[0143] (Example III-1) In the annealing step, the mixture was adjusted so that the amount of magnesium oxide was 0.1 mass% relative to 100 mass% of the total amount of the first fired body and magnesium oxide, and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type SiAlON phosphor was obtained.
[0144] (Example III-2) In the annealing step, the mixture was adjusted so that the amount of magnesium oxide was 0.5 mass% relative to 100 mass% of the total amount of the first fired body and magnesium oxide, and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type SiAlON phosphor was obtained.
[0145] (Example III-3) In the annealing step, the mixture was adjusted so that the amount of magnesium oxide was 1 mass% relative to the total amount of the first fired body and magnesium oxide (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type SiAlON phosphor was obtained.
[0146] (Comparative Example III-2) In the annealing step, the mixture was adjusted so that the amount of magnesium oxide was 5% by mass relative to the total amount of the first fired body and magnesium oxide (100% by mass), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type SiAlON phosphor was obtained.
[0147] (Example III-4) In the annealing step, the mixture was adjusted so that the amount of strontium carbonate was 0.1 mass% relative to the total amount of the first fired body and strontium carbonate (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type sialon phosphor was obtained.
[0148] (Example III-5) In the annealing step, the mixture was adjusted so that the amount of strontium carbonate was 0.5 mass% relative to the total amount of the first fired body and strontium carbonate (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type sialon phosphor was obtained.
[0149] (Example III-6) In the annealing step, a mixture was prepared so that the amount of strontium carbonate was 1 mass% relative to the total amount of the first fired body and strontium carbonate (100 mass%), and then the mixture was heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type sialon phosphor was obtained.
[0150] (Example III-7) In the annealing step, the mixture was adjusted so that the amount of strontium carbonate was 1.5 mass% relative to the total amount of the first fired body and strontium carbonate (100 mass%), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type sialon phosphor was obtained.
[0151] (Comparative Example III-3) In the annealing step, a mixture was prepared so that the amount of strontium carbonate was 5% by mass relative to the total amount of the first fired body and strontium carbonate (100% by mass), and then heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-type sialon phosphor was obtained.
[0152] (Comparative Example III-4) In the annealing step, a mixture was prepared so that the amount of lithium carbonate was 0.5% by mass relative to 100% by mass of the total amount of the first fired body and lithium carbonate, and then the mixture was heated under an argon gas atmosphere. In the same manner as in Comparative Example III-1, a europium-activated β-sialon phosphor was obtained.
[0153] (Comparative Example III-5) A standard sample of β-type Sialon phosphor (manufactured by Sialon Corporation, NIMS Standard Green lot No. NSG1301) was used as the phosphor of Comparative Example III-5.
[0154] <Measurement of alkaline earth metal element (magnesium, strontium and lithium) content> The contents of alkaline earth metal elements (magnesium, strontium and lithium) of each of the europium-activated β-sialon phosphors prepared in Examples III-1 to III-7 and Comparative Examples III-1 to III-5 were measured by the following method. The results are shown in Table 3.
[0155] <Magnesium, strontium and lithium content> The contents of magnesium, strontium and lithium in the europium-activated β-sialon phosphor were measured by the following procedure. The phosphor was dissolved by the pressurized acid decomposition method to prepare a sample solution. The obtained sample solution was subjected to quantitative elemental analysis using an ICP emission spectrometer (manufactured by Rigaku Corporation, product name: CIROS-120) to measure the contents. The detection limits of magnesium (Mg), strontium (Sr) and lithium (Li) were each 100 ppb.
[0156] [Evaluation of europium-activated β-type sialon phosphor] The absorptivity when irradiated with an excitation light having a wavelength of 455 nm, internal quantum efficiency, chromaticity X, chromaticity Y, and absorptivity when irradiated with an excitation light having a wavelength of 600 nm for each of the europium-activated β-sialon phosphors prepared in Examples III-1 to III-7 and Comparative Examples III-1 to III-5 were evaluated by the methods described below. The results are shown in Table 3.
[0157] <Absorptivity and internal quantum efficiency> The absorptance (excitation light absorptance) and internal quantum efficiency of the phosphor when irradiated with excitation light of 455 nm wavelength were calculated by the following procedure. First, the phosphor to be measured was filled into a concave cell so that the surface was smooth, and the cell was attached to the opening of an integrating sphere. Monochromatic light having a wavelength of 455 nm was split from a Xe lamp, which is a light emission source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The monochromatic light, which is the excitation light, was irradiated onto the phosphor to be measured, and the fluorescence spectrum was measured. A spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., product name: MCPD-7000) was used for the measurement.
[0158] From the obtained fluorescence spectrum data, the emission intensity of the phosphor was determined. Also, from the obtained fluorescence spectrum data, the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. Also, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm.
[0159] From the above calculation results, the absorptance of the 455 nm excitation light, the internal quantum efficiency, and the external quantum efficiency of the phosphor to be measured were calculated based on the following formulas. Absorption rate of 455 nm excitation light = ((Qex-Qref) / Qex) x 100 Internal quantum efficiency = (Qem / (Qex-Qref)) x 100 External quantum efficiency = (Qem / Qex) x 100 From the above formula, the relationship between the external quantum efficiency, the absorptance of 455 nm excitation light, and the internal quantum efficiency can be expressed as follows: External quantum efficiency = 455 nm light absorptance × internal quantum efficiency
[0160] <Chromaticity X and Y> The chromaticity X and Y were determined from the spectral data in the wavelength range of 465 to 780 nm of the fluorescence spectrum by calculating the x value (chromaticity X) of the CIE chromaticity coordinates and the y value (chromaticity Y) of the CIE chromaticity coordinates in the XYZ color system defined in JIS Z8781-3:2016 in accordance with JIS Z8724:2015.
[0161] <600nm light absorption rate> A standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was set at the side opening of the integrating sphere. Monochromatic light separated into wavelengths of 600 nm from a light emission source (Xe lamp) was introduced into this integrating sphere via an optical fiber, and the reflected light spectrum was measured with a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). At that time, the number of incident light photons (Qex(600)) was calculated from the spectrum in the wavelength range of 590 to 610 nm.
[0162] Next, the concave cell was filled with β-SiAlON phosphor so that the surface was smooth, and then it was set in the opening of the integrating sphere. Monochromatic light with a wavelength of 600 nm was irradiated, and the incident reflected light spectrum was measured with a spectrophotometer. The incident reflected light photon count (Qref(600)) was calculated from the obtained spectrum data. The incident reflected light photon count (Qref(600)) was calculated in the same wavelength range as the incident light photon count (Qex(600)). The 600 nm light absorptance was calculated from the obtained two types of photon counts based on the following formula. 600 nm light absorption rate = ((Qex(600)-Qref(600)) / Qex(600)) x 100
[0163] The measured values of the phosphor's absorptance, internal quantum efficiency, external quantum efficiency, fluorescence peak wavelength and half-width, chromaticity X, and chromaticity Y may vary when the manufacturer of the measuring device, production lot number, etc., are changed. Therefore, the values measured by the measuring method described in this specification are used as the various measured values. However, when the manufacturer of the measuring device, production lot number, etc., are changed, each measured value can be corrected using the measured value of the standard sample of the β-type Sialon phosphor described above as the reference value. As the standard sample for obtaining the reference value, the standard sample of the β-type Sialon phosphor listed above as Comparative Example III-5 can be used.
[0164] [Table 3] [Industrial Applicability]
[0165] According to the present disclosure, it is possible to provide a europium-activated β-sialon phosphor having excellent internal quantum efficiency.
Claims
1. A europium-activated β-type sialon phosphor containing at least one element selected from the group consisting of yttrium, titanium, and gadolinium, the total content of said at least one element being more than 0 ppm and less than 1000 ppm.
2. 2. The europium-activated β-sialon phosphor of claim 1, wherein said at least one element is yttrium.
3. 2. The europium-activated β-sialon phosphor of claim 1, wherein said at least one element is titanium.
4. 2. The europium-activated β-sialon phosphor of claim 1, wherein the at least one element is yttrium and titanium.
5. the at least one element comprises at least one of yttrium and titanium; 5. The europium-activated β-sialon phosphor according to claim 1, wherein the total content of the yttrium and the titanium is 0.1 to 500 ppm.
6. 5. The europium-activated β-sialon phosphor according to claim 1, wherein the at least one element contains at least one of yttrium and titanium, and the absorptance of the phosphor with respect to excitation light having a wavelength of 600 nm is 5% or less.
7. 2. The europium-activated β-sialon phosphor of claim 1, wherein said at least one element is gadolinium.
8. 8. The europium-activated β-sialon phosphor according to claim 7, wherein the gadolinium content is 0.1 to 300 ppm.
9. 9. The europium-activated β-sialon phosphor according to claim 7, which has an absorptance of 6% or less for excitation light having a wavelength of 600 nm.
10. A europium-activated β-type sialon phosphor containing alkaline earth metal elements, the total content of the alkaline earth metal elements being more than 0 ppm and less than 1000 ppm.
11. 11. The europium-activated β-sialon phosphor according to claim 10, wherein the alkaline earth metal element is magnesium or strontium.
12. 12. The europium-activated β-sialon phosphor according to claim 10, wherein the total content of the alkaline earth metal elements is 0.1 to 500 ppm.
13. The europium-activated β-sialon phosphor according to any one of claims 10 to 12, having an absorptance of 7% or less for excitation light having a wavelength of 600 nm.
14. A light emitting device comprising: a light emitting element that emits primary light; and a wavelength converter that absorbs a portion of the primary light and emits secondary light having a wavelength longer than the wavelength of the primary light, A light emitting device, wherein the wavelength converter comprises the europium-activated β-sialon phosphor according to any one of claims 1 to 13.
Citation Information
Patent Citations
High-brightness large-particle-size beta-SiAlON:Eu<2+> green emitting phosphor and preparation method thereof
CN106281317A
Phosphor and manufacturing method thereof, white light emitting device, surface light source device, display device, and lighting device
JP2013519750A
Red phosphor, white light emitting device, display apparatus and illumination apparatus
US20140376259A1
Silicon nitride powder for siliconitride fluorescent material, sr3al3si13o2n21 fluorescent material and ?-sialon fluorescent material both obtained using same, and processes for producing these
WO2012023414A1
MANUFACTURING METHOD OF β SIALON PHOSPHOR
JP2017002278A
